Investigating democracy and social capital in India - Blomkvist, Hans; Swain, Ashok (2001)
Social capital refers to trusts, networks and norms shared by a group of actors that enable them to act together more effectively to pursue shared objectives. The study of civil society and social capital allows for the study of conflict over resources or group domination. The theoretical significance of social capital is not that it will necessarily lead to societal peace and harmony, nor does its study necessarily exclude politics and political conflict. The point is to focus attention on non-material resources at the micro-level and their possible impact on the macro-level. Whether these resources, the social capital, are structured on the basis of class, caste, religious group or geographical belonging is open to empirical investigation. - Reproduced
Keywords: Social capital - India; Infrastructure development - India; Social capital